Pentingnya Motivasi Dalam Menumbuhkan Minat Berwirausaha - Purwaningsih, Dewi (Rifa'Institute, 2021)
Strong motivation in running a business is needed in addition to the intentions and enthusiasm that exist in an entrepreneur. With a strong motivation can encourage entrepreneurs to start a business well to achieve the target to be determined. This study aims to explain and explain the importance of motivation in growing interest in entrepreneurship. The method used in this study is a qualitative approach method with descriptive analytical and explanatory studies as well as data collection through literature studies, literature / and related documentation related to the importance of motivation in growing interest in entrepreneurship. High motivation in a person will encourage the entrepreneur to carry out all activities and activities in entrepreneurship. With the existing motivation will arise the will and interest of entrepreneurs to run their business in order to continue to grow and achieve the goals that have been set.